2014
DOI: 10.1186/1471-2458-14-363
|View full text |Cite
|
Sign up to set email alerts
|

Individual, facility, and program factors affecting retention in a national weight management program

Abstract: BackgroundHigh attrition is a common problem for weight loss programs and directly affects program effectiveness. Since 2006, the Veterans Health Administration (VHA) has offered obesity treatment to its beneficiaries through the MOVE! Weight Management Program for Veterans (MOVE!). An early evaluation of this program showed that attrition rate was high. The present study examines how individual, facility, and program factors relate to retention for participants in the on-site MOVE! group program.MethodsData f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 24 publications
5
41
1
Order By: Relevance
“…11 Factors that have been identified as influencing retention in weightloss trials include age, sex, race, distance to intervention site, cognitive impairment, occupational status, education, socioeconomic status, smoking, physical activity level and depression. 9,[16][17][18][19] A review of 50 studies of AAs in clinical trials identified barriers to retention including lack of a study partner, lower educational level, and lack of compensation. 20 An earlier study conducted by our team found that a decentralized CBPR approach led to intervention…”
Section: Methodsmentioning
confidence: 99%
“…11 Factors that have been identified as influencing retention in weightloss trials include age, sex, race, distance to intervention site, cognitive impairment, occupational status, education, socioeconomic status, smoking, physical activity level and depression. 9,[16][17][18][19] A review of 50 studies of AAs in clinical trials identified barriers to retention including lack of a study partner, lower educational level, and lack of compensation. 20 An earlier study conducted by our team found that a decentralized CBPR approach led to intervention…”
Section: Methodsmentioning
confidence: 99%
“…A range of factors has been associated with risk of participant attrition in longitudinal studies (Blanton et al 2006; Brown et al 2006; Clark et al 1996; Dalle Grave et al 2005; Fabricatore et al 2009; Fitzpatrick et al 2014; Honas et al 2003; Kong et al 2010; Manson et al 2011; McGuigan et al 2003; O–Brien et al 2012; WarrenFindlow et al 2003; Williams et al 2008). With respect to lifestyle interventions to promote weight loss, multiple studies have attempted to identify baseline factors that predict the risk of participant attrition (Fabricatore et al 2009; Fitzpatrick et al 2014; Honas et al 2003; Rothberg et al 2015; Spring et al 2014). Most lifestyle intervention projects that investigated this issue had relatively small sample size with younger age being the most consistent predictor for attrition in those studies.…”
mentioning
confidence: 99%
“…Finally, these findings highlight that phone-based coaching is a viable treatment modality for increasing access. Moving forward, combining evidence from this and other evaluations to date, [46][47][48][49][50] the VA can continue their leadership in developing effective and cutting-edge population-based initial treatment and long-term continuous-care weight management programs for US veterans.…”
Section: Discussionmentioning
confidence: 99%